Analisis Kualitas Pelayanan, Kepercayaan, Dan Harga Terhadap Kepuasan Konsumen Berbelanja Online Di Shopee (Studi Pada Mahasiswa Fakultas Ekonomi Universitas 17 Agustus 1945 Samarinda) - Taghfirul Azhima Yoga Siswa3, Ricka Asmawati1 LCA Robin Jonathan2 (EKONOMIA, 2020)
ABSTRACTThe purpose of this research are:  1) To find out and analyze the effect of service quality on customer satisfaction in shopping online at Shopee. 2) To find out and analyze the effect of trust on customer satisfaction in shopping online at Shopee. 3) To find out and analyze the effect of prices on customer satisfaction in shopping online at Shopee. 4) To find out and analyze the effect of service quality, trust, and price together on customer satisfaction in shopping online at Shopee. The theory used in this research is the quality of service, trust, price, and customer satisfaction.This research conducted in Faculty of Economics, August 17th, 1945 Samarinda. Samples taken as many as 100 respondents with a Non-Probability Sampling the sampling technique used purposive sampling. Collecting data by questionnaires using Likert scale to measure each indicator. The analytical tool in the study using multiple linear regression analysis by using the tools of statistical program SPSS v20.               The results of this study show that: 1) The variable of service quality has a significant effect on customer satisfaction shopping online at Shopee. 2) The variable trust has a significant effect on customer satisfaction shopping online at Shopee. 3) The variable price has a significant effect on customer satisfaction shopping online at Shopee. 4) The variable service quality, trust, and price together - a significant effect on consumer satisfaction shopping online at Shopee.